The serum levels of angiopoietin‐like protein 3 and 4 in type 2 diabetic patients with and without metabolic syndrome compared to the control group - Sharabeh Hezarkhani; Aytekin Hajighaderi; Sara Hosseinzadeh; Naser Behnampour; Gholamreza Veghari; Farshid Fathabadi; Zahra Hesari; Hamid Reza Joshaghani (Endocrinology, Diabetes & Metabolism, 2024)
Abstract Introduction ANGPTLs (Angiopoietin‐like proteins) 3 and 4 play an important role in the development of type 2 diabetes. These glycoproteins affect the modulation of glucose and lipid metabolism. They inhibit lipoprotein lipase (LPL) activity and provoke lipolysis. This study was aimed to investigate the protein levels of ANGPTL3 and 4 in the serum of type 2 diabetic patients with metabolic syndrome in comparison to the type 2 diabetic patients without metabolic syndrome and the control group. Methods Three groups of individuals were included in this study; Group I: 47 patients with type 2 diabetes and metabolic syndrome; Group II: 25 patients with type 2 diabetes without metabolic syndrome; Group III: 40 non‐diabetic healthy people without metabolic syndrome as a control group. After collection of 5 mL fasting blood samples, serum concentrations of fasting blood sugar (FBS), cholesterol (Chol), triglyceride (TG), HDL‐C (High‐density lipoprotein‐Cholesterol) and LDL‐C (Low‐density lipoprotein‐Cholesterol) were measured by the enzymatic method; blood pressure (BP), height and weight with stadiometers; and ANGPTL3 and 4 by the enzyme‐linked immunosorbent assay (ELISA). Results The serum levels of ANGPTL3 was significantly different among our three groups (p = .000). In patients with type 2 diabetes and metabolic syndrome (Group I), ANGPTL3 and 4 levels were lower than the control group. The serum levels of the parameters evaluated in this study (except HDL‐C) was lower in the group II in comparison with the group I, and this difference was significant for TG, Chol, BP and BMI between these two groups. Also, our results revealed that there was a negative correlation between FBS, TG, Chol, LDL‐C and BMI with ANGPTL3 and 4. While, there was a significant positive correlation between ANGPTL4 and ANGPTL3. Conclusion Altogether, our findings suggest that the decreased levels of ANGPTL3 and 4 may be a causative factor for type 2 diabetes.